Characterization of rich husk ash mineral addition to concrete (Research, Society and Development, 2019)
The incorporation of residues in cement-based mixtures can bring technical advantages related to the use of organic matter available in nature. The objective of this research is to replace percentages of cement by weight per rice husk ash (CCA), since the relevance of this research is based on the sustainability generated using ash. The methodological process consisted in characterizing the CCA through an experimental program. The results presented were performed using XRD test, laser grading, B.E.T. method and fire loss, in which the presence of silica in a crystalline state with low amorphization is shown (a little amorphic structure), exhibiting that the rice husk ash analyzed has moderate pozzolanic properties. In addition, the CCA has a higher specific surface area and greater particle size when compared to cement, thus emphasizing the need for an appropriate milling process and superplasticizer additives for it uses as a substitution of percentages of bulk cement in traces of conventional concrete.